Comparative structure analysis of the ETSi domain of ERG3 and its complex with the E74 promoter DNA sequence. Corrigendum. Issue 5 (2nd May 2019) - Sharma, Ruby; Gangwar, Shanti P.; Saxena, Ajay K.
Abstract : A correction to the article by Sharma et al. [(2018), Acta Cryst. F74, 656–663 ] is published. Abstract : The article by Sharma et al. [(2018), Acta Cryst. F74, 656–663] is corrected.